Ceftriaxone pretreatment protects rats against cerebral ischemic injury by attenuating microglial activation-induced IL-1β expression. (2nd September 2014) - Lujia, Yang; Xin, Li; Shiquan, Wang; Yu, Chen; Shuzhuo, Zhang; Hong, Zhang
<x xml:space="preserve">Abstract</x> Background: Although the neuroprotective effect of ceftriaxone (CTX) has been reported, the underlying mechanisms are still uncertain. In this study, we investigated if rats recover better from CTX pretreatment against cerebral ischemia by inhibiting the inflammatory response. Methods: Rats were pretreated with CTX (200 mg/kg, 1/day, i.p.) for 5 d. At 24 h after the end of the last CTX pretreatment, focal cerebral ischemia was induced by middle cerebral artery occlusion (MCAO) for 120 min in male Sprague Dawley rats. The neurological deficit scores (NDS) and infarct volumes were evaluated. Microglia cells were observed by immunofluorescence staining and IL-1β was assayed by ELISA and Western Blot. Results: The results showed that CTX pretreatment improved the neurological deficit scores and decreased the infarct volumes 24 h after reperfusion. The activation of microglia cells was reduced and the expression of IL-1β was partially inhibited 24 h after reperfusion. Conclusion: These findings demonstrate that CTX pretreatment may provide a neuroprotective effect against transient cerebral ischemic injury, partially inhibit in microglial activation and reduce the expression of IL-1β.